Segmentation of gastronomic consumers following Instagram influencers based on destination preferences and the effect of Covid-19 on their consumption - Szakály, Orsolya (Marketing & Menedzsment, 2022)
THE AIM OF THE PAPER The aim of the study is to explore the impact of gastronomic influencers on Instagram on consumer decision before choosing a restaurant. It also examines the role of the characteristics of destination in consumer decision-making process. The article also highlights the impact of the Covid-19 Pandemic and its impact on consumers’ decision process in that context. METHODOLOGY In order to analyze the main research questions, a quantative survey with 329 valid responses was implemented and descriptive statistics, relationship analysis methods and linear regression were used to answer the research questions. The research question also required the use of a subsample (n=185) in which respondents who are willing to travel for gastronomic purposes were examined during the Pandemic. MOST IMPORTANT RESULTS According to the results, the collection of information from gastronomic influencers on the Instagram interface is popular among the respondents, and the influencers’ activity has a positive effect on the number of visitors to the destinations. Thus, it can be said that the relationship between the influencer and the destination is characterized by a significant, medium strength relationship. Furthermore, the results also revealed that the Pandemic has led to an increase in consumers’ intentions to consume in restaurants. RECOMMENDATIONS As social media plays an increasingly important role in the decision-making process, it is important that professionals, service providers and researchers explore the views of consumers in the context under study. The results are highlighted in terms of destination development and in terms of consumer behavior.